Coordination Polymers Involving Organotin Derivatives as Lewis Acids - Shukla, P.R.; Ahmad, Nihal; Sharma, M.C.; Narain, Gopal (Asian Journal of Chemistry, 2010)
Nine complexes of αα´-dipyridyldisulphide with some diorganotin derivatives possessing the general formulae [RSnL-]nX2n where R ═ phenyl, benzyl, n-butyl and X═Cl-. ClO4– and NO3– have been prepared and assigned polymeric octahedral structures on the basis of IR and 1H NMR spectral studies. The ligand behaves as tetradentate in nature coordinating through its both sulphur and nitrogen atoms but steric factors prevent the coordination of all four donors to the same tin atom and hence polymeric octahedral structures are suggested in which the organic group is bonded axially to the tin atom.